INVESTIGATION OF STUDENT?óÔé¼ÔäóS WORK ON FRACTION?óÔé¼ÔäóS IMPLEMENTATION BASED ON THE JOURNAL ENTITLED ?óÔé¼?ôA STUDY ON THE ABILITY OF SIXTH GRADE STUDENTS IN TIBETAN AREAS TO SOLVE MATH PROBLEMS?óÔé¼?Ø - Pramasdyahsari, Agnita Siska (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2015)
This study aims to analyse the student?óÔé¼Ôäós performance in solving fractions and explore the students?óÔé¼Ôäó understanding related with fraction. The subjects of this study are 2 students of grade 6 and 1 student of grade 7. In this case, as an observer who implement the mathematics problem based on the questions which is adapted from the journal, it just analyse about the students?óÔé¼Ôäó work related to the students?óÔé¼Ôäó understanding about fraction. No matter how the students?óÔé¼Ôäó ways and their methods to solve the problem which is provided, whether it is true or vice versa, because the question enable of open answer, the important thing is we will recognise the students?óÔé¼Ôäó understanding about fraction. Through analyse from their worksheet and interview, it can be said that there are several reasons why they did as they wrote in. Keywords: Fraction,?é?á Understanding, Sixth?é?á grade students.